Keputusan Pembelian Minuman Yakult Ditinjau Dari Distribusi, Diferensiasi, Gaya Hidup, Dan Kualitas Produk - Permata Citra, Elisa Sulistia; Ida Ayu Kade, Rachmawati Kusasih (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2020)
The purpose of this study was to examine the effect of distribution, differentiation, lifestyle, and product quality on the purchase decision for Yakult drinks in Solo City. The population used in this study is consumers of Yakult fermented milk in Solo. The data used in this study are primary data obtained from questionnaires. The number of samples taken were 97 respondents. The technique used in sampling is the Non Random Sampling technique with multiple linear regression analysis and hypothesis testing consists of the t test, the coefficient of determination (R²). The results of this study indicate that the Distribution variable (X1) and the Differentiation variable (X2) do not significantly influence the purchasing decisions of Yakult brand fermented milk in Solo City, Lifestyle (X3) and Product Quality (X4) significantly influence the purchase decision of the Yakult brand fermented milk in Solo city.